Predicting the Risk of In-Hospital Major Adverse Cardiovascular Events in Chronic Total Occlusion Percutaneous Coronary Intervention: The PROGRESS-CTO MACE Score - Simsek, Bahadir; Kostantinis, Spyridon; Karacsonyi, Judit; Alaswad, Khaldoon; Krestyaninov, Oleg; Khelimskii, Dmitrii; Davies, Rhian; Rier, Jeremy; Goktekin, Omer; Gorgulu, Sevket; ElGuindy, Ahmed; Chandwaney, Raj; et al. (ELSEVIER SCIENCE INC, 2022)
34th Annual Symposium on Transcatheter Cardiovascular Therapeutics (TCT), Boston, MA, SEP 16-19, 2022